On the meaning of some terms used in the documents of the Tupamarista revolution, 1780-1783 - Szeminski, Jan (1980)
The civil war is the most drastic form of social conflict and therefore it is to be expected that in the documents that have arisen in relation to it, the reflection of the social differences perceived by its participants will be the most complete. Already in 1972, I formulated a hypothesis about the coexistence of four parallel hierarchies, hierarchies of castes, estates, cultures and classes (social layers). It is assumed that the levels of the four hierarchies were named in a similar way, or even in the same way, and therefore the existence of several hierarchies can be recognized only when one and the same person is named simultaneously with different terms, e.g.: rancher, Indian, Spanish, cholo.